In vitro pharmacokinetic drug interaction study Of combination of antiretroviral and Antimalarial drugs - SUNITHA G.N,; B.M.V SWAMY,; D. SATYAVATI DULIPALIA,; GIRISH GUDI, (International Journal of Pharma and Bio Sciences, 2018)
Malarial infection and Human Immunodeficiency Viral infection (HIV) do occur commonly. The World Health Organization (WHO) recommends the standard Artemisinin-based therapy for malaria which usually consists of Artemether, Artesunate or Dihydroartemisinin with non-artemisinin derivatives like Amodiaquine (ADQ), Lumefantrine, and Mefloquine. These antimalarials are administered in combination to maximize the efficacy. In such case, the protease inhibitor (PI)-based combination of ARV therapy is usually second or third line regimen and Lopinavir/Ritonavir is the most common PI. Generally, the PIs inhibit CYP3A4 and artemisinins are majorly metabolised by CYP3A4 with high potential for pharmacokinetic (PK) drug interactions. Hence the present research is an attempt to evaluate the PK interactions between antimalarials and antiretrovirals through in vitro PK studies, such as Cytochrome P450 (CYP) inhibition studies, and to predict the potential for in vivo drug-drug interactions (DDI) using FDA’s basic model.The inhibition of cytochromes P450 (CYPs) CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4 in pooled human liver microsomes was evaluated for antimalarial (AM) drugs and antiretroviral (ARV) drugs independently and also in combination. The CYP inhibition data demonstrated that the AM drugs inhibit the evaluated CYP enzymes to a lesser extent either independently or in combination indicating that they are weak inhibitors of the CYP enzymes. Ritonavir was observed to be a potent inhibitor of CYP3A4 and CYP2C9. However, the antimalarial drugs in combination with Ritonavir are strong inhibitors of CYP3A4 and CYP2C9 and this indicates the major role of Ritonavir in the CYP inhibition. The AM drugs in combination with Lopinavir are weak inhibitors of the evaluated CYP’s. The R1 value of >1.02 for Ritonavir and AM drug combinations of Artemether-Lumefantrine, Artesunate-Amodiaquine and Atovaquone-Proguanil with Ritonavir suggest the liability of DDI and warrant the need of human in vivo pharmacokinetic studies.